2000
DOI: 10.2737/fpl-gtr-118
|View full text |Cite
|
Sign up to set email alerts
|

Drying hardwood lumber

Abstract: Drying Hardwood Lumber focuses on common methods for drying lumber of different thickness, with minimal drying defects, for high quality applications. This manual also includes predrying treatments that, when part of an overall quality-oriented drying system, reduce defects and improve drying quality, especially of oak lumber. Special attention is given to drying white wood, such as hard maple and ash, without sticker shadow or other discoloration. Several special drying methods, such as solar drying, are desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 8 publications
(1 reference statement)
0
29
0
4
Order By: Relevance
“…Graphs of the same form as Figure 12 have subsequently been published, presumably based on the completed data set, and no longer considered to be under revision and correction (Voorhies and Loughborough 1943;Smith 1947Smith , 1963Denig et al 2000).…”
Section: Figure 12 Emc-humidity-temperature Chart (Us Department Omentioning
confidence: 99%
See 3 more Smart Citations
“…Graphs of the same form as Figure 12 have subsequently been published, presumably based on the completed data set, and no longer considered to be under revision and correction (Voorhies and Loughborough 1943;Smith 1947Smith , 1963Denig et al 2000).…”
Section: Figure 12 Emc-humidity-temperature Chart (Us Department Omentioning
confidence: 99%
“…Figures of this type have been widely published (Peck 1932;FPL 1935FPL , 1940FPL , 1944FPL , 1951FPL , 1955; U.S. Army Air Forces 1944; Denig et al 2000). Figure 14 shows relative humidity versus vapor pressure with curves of constant EMC and of constant temperature (Loughborough 1942).…”
Section: Several Variations Onmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Elustondo and Oliveira (2009) reported that the energy consumption to evaporate cold water used for humidifi cation in small kilns accounts for more than 15 % of the total energy consumption, and if high both dry-bulb and wet-bulb temperatures (over 60 °C) are used, it can reach almost 50 %. Generally, in industrial conditions, the percentage of energy needed for heating of air and wood is relatively low (around 5 %, according to Denig et al, 2000). When oscillations of drying parameters are used, the humidifi cation system will be switched on more frequently than with conventional schedules, so it is expected that the energy consumption for heating of air and wood in those schedules will also be somewhat higher, but still low compared to the total energy consumption.…”
Section: Rezultati I Raspravamentioning
confidence: 99%